BCL10 – Bridging CARDs to Immune Activation - Gehring, Torben; Seeholzer, Thomas; Krappmann, Daniel (Frontiers in Immunology, 2018)
After the first description of BCL10 in 1999 many studies have unraveled its key functions for channeling adaptive and innate immune signaling downstream of CARMA/CARD scaffold proteins. While T- and B-cell antigen receptor (TCR/BCR) signaling induces the recruitment of pre-assembled BCL10-MALT1 complexes to the lymphocyte-specific CARMA1/CARD11-BCL10-MALT1 (CBM-1) signalosome, alternative CBM complexes utilize different CARMA/CARD scaffolds in distinct innate or inflammatory pathways. With 233 amino acids encoding for an N-terminal CARD and a C-terminal Ser/Thr-rich region, BCL10 constitutes the smallest subunit in all CBM signalosomes. By forming filaments, BCL10 aggregates into higher-order clusters that mediate and amplify signaling upon stimulation leading to activation of the MALT1 protease and canonical NF-kB and JNK signaling. Moreover, BCL10 is prone to extensive post-translational regulation involving phosphorylation, ubiquitination, MALT1-catalyzed cleavage and degradation. Through these feed-back or feed-forward events BCL10 integrates positive and negative regulatory processes that govern the function as well as the dynamic assembly, disassembly and destruction of CBM complexes. Thus, BCL10 is a critical regulator for activation as well as termination of immune cell signaling, revealing that the role of BCL10 goes far beyond a mere linking factor in the CBM complexes.